Use of Information and Communication Technologies for Sustainable Agricultural Development among Rural Farmers in Ekiti State Nigeria - Toluwase, S. O. W; A. O., Awoyemi (Advances in Social Sciences Research Journal, 2017)
The study assessed the use of Information and Communication Technologies (ICTs) for sustainable agricultural development among rural farmers of Ekiti State, Nigeria. The specific objectives were to describe the socio-economic characteristics of rural farmers; determine the availability and accessibility of various ICTs to farmers study; determine the perception of farmers concerning ICTs, ascertain the types and frequency of use of ICTs in receiving agricultural information; evaluate the level of satisfaction with regard to the information received through various ICTs; and identify some constraints militating against the use of ICTs in the study area. The study was carried out in Ekiti State where one hundred and twenty farmers were randomly selected from the ADP zones in the states. Data were collected from rural farmers using structured interview schedule and were subjected to descriptive and inferential statistics. The results of the analysis revealed that the average age of the farmers was 42.6 years. Majority (94.2%) of the respondents were males who were married and (93.3%) are Christians. The major ICTs commonly used among the farmers were GSM mobile phone, radio, television and newspapers. Rural farmers in the area had a favourable perception about ICTs. Respondents in the area considered radio and television to be the most relevant sources of agricultural information to them. Results of the data also shows that age (r = 0.138, p<0.01) and Cosmo politeness (.r2=0.045; P, 0.05) of farmers have significant relationship with the use of ICTS for sustainable agricultural deployment. It was recommended that local language should be used to disseminate agricultural information via ICTS to rural farmers.